Unexpected tubal pregnancy at 13 weeks' gestation that was treated with laparoscopic surgery under massive hemoperitoneum - Mirang Kim; Kosuke Hiramatsu; Kaoru Fukui; Kyoka Amemiya (Wolters Kluwer Medknow Publications, 2019)
An advanced second trimester tubal pregnancy is rarely encountered because almost all ecopic pregnancy are diagnosed at an early stage. Transvaginal sonography is simple and useful for diagnosing ectopic pregnancy. However, diagnosing the site of ectopic pregnancy and gestational age is sometimes difficult. We experienced a case of an unexpected 13-week tubal pregnancy that was not able to be diagnosed with an accurate pregnancy site and gestational age by transvaginal sonography before surgery. Under massive hemoperitoneum, forceps penetrated the area of pregnancy, which led to further massive bleeding. However, laparoscopic surgery was able to be performed. The findings in our case suggest the importance of examining with transabdominal sonography, especially in an emergency and in advanced tubal pregnancy. In addition, careful manipulation of forceps is required when the ectopic pregnancy mass is large.